Prediction of material requirements for network construction using apriori algorithm - Layli Nur'Aini; Mukhtar Hanafi; Emilya Ully Artha (Borobudur Informatics Review, 2022)
PT XYZ is one of the providers of fixed broadband development services spread throughout Indonesia. What often happens is the lack of material availability and the long pre-order process, thus hampering projects that have been agreed upon for completion. The a priori algorithm is one of the data mining algorithms in the association method, which is looking for relationships between interrelated items. This research uses the help of RStudio software. This prediction is expected to help to prepare material stock in the warehouse so as to prevent material vacancies in the warehouse. The results of this study are in the form of a rule that meets the minimum support value (a measure that shows how much dominance an item/item set is from the entire transaction) of 27.84%, minimum confident (a measure that shows the relationship between 2 items conditionally) of 27.84%. 84.48% and the lift ratio (a measure to see whether or not the association rules are formed) is > 1.